(untitled) (Sains Humanika, 2006)
The purpose of this study is to examine computer usage factors, which are attitude, literacy, and facilities among education graduate students in Universiti Teknologi Malaysia, Skudai. From these factors, this research is also to determine the main factor of computer usage among students. In addition, students’ readiness towards online learning is studied. This study also examined whether there is a significant correlation between computer usage factors and graduate students’ readiness towards online learning. Questionnaires were employed to gather related data. Descriptive analyses and two-tailed Pearson correlation test with significance at α = 0.01 level were conducted to answer the research questions. The findings showed that students have positive attitude (mean = 3.29), possess average computer literacy (mean = 2.59) and agree that computer facilities at the place of study (mean = 2.64) were insufficient. From these three factors, attitude (mean = 3.29) is the main factor for computer usage among graduate students. It was found that students are not well prepared toward online learning (mean = 2.93). However, average and low correlation were found between attitude (r = 0.385) and computer literacy (r = 0.267) with students’ readiness towards online learning. Facilities at the place of study (r = 0.415), on the other hand, showed an average correlation with students’ readiness towards online learning.